Combinations of Plant Species for Rotation With Onion Crops: Effects on the Light Fraction, Carbon, and Nitrogen Contents in Granulometric Fractions of the Soil Organic Matter - Giumbelli, Lucas Dupont; Loss, Arcângelo; Kurtz, Claudinei; Mafra, Álvaro Luiz; Piccolo, Marisa de Cássia; Torres, osé Luiz Rodrigues; Lourenzi, Cledimar Rogério; Brunetto, Gustavo; Comin, Jucinei José (Journal of Agricultural Studies, 2021)
The conversion of conventional tillage system (CTS) into no-tillage system (NTS) for onion crops with use of soil cover crops increases carbon and nitrogen contents in the soil aggregates. The objective of this work was to evaluate the effects of combinations of different plant species and soil management systems using rotation with soil cover crops for onion crops on the light organic matter (LOM), carbon (C), and nitrogen (N) contents in the organic matter granulometric fractions in soil macroaggregates and bulk soil. A nine-year experiment (2007-2016) was conducted using the treatments (T): maize-onion in NTS (T1); soil cover crops (winter)-onion in NTS(T2); maize-winter grasses-onion in NTS (T3); velvet bean-onion in NTS (T4); millet-soil cover crops (winter)-onion in NTS (T5); velvet bean-rye-onion in NTS (T6); maize-onion in CTS (T7); intercropped soil cover crops (summer)-onion in NTS (T8). C and N contents in the LOM, particulate organic C and N (POC and PON), and mineral- associated C and N (MOC and MON) were evaluated in soil macroaggregates (8.0 to 2.0 mm) and bulk soil (<2.0 mm) from the 0–5 cm, 5–10 cm, and 10–20 cm layers. High diversity and combinations of plant species in T2-T6, and T8 resulted in higher POC and MON contents in aggregates, and higher MOC and PON contents in bulk soil, when compared to T1 and T7. T2 was a better option to increase LOM and POC contents in aggregates (0-5 cm). The evaluation of POC (0–5 cm), PON, and MON (0-10 cm) contents in soil aggregates showed more significant differences between the treatments than the contents found in bulk soil. The onion crops under NTS combined with use of rotations with soil cover crops were more efficient to improve the evaluated soil attributes than those under CTS.